Emerging Role of HMGB1 in the Pathogenesis of Schistosomiasis Liver Fibrosis - Vicentino, Amanda R. R.; Carneiro, Vitor C.; Allonso, Diego; Guilherme, Rafael de Freitas; Benjamim, Claudia F.; dos Santos, Hílton A. M.; Xavier, Fabíola; Pyrrho, Alexandre dos Santos; Gomes, Juliana de Assis Silva; Fonseca, Matheus de Castro; de Oliveira, Rodrigo C.; Pereira, Thiago A.; et al. (Frontiers in Immunology, 2018)
In chronic schistosomiasis, liver fibrosis is linked to portal hypertension, which is a condition associated with high mortality and morbidity. High mobility group box 1 (HMGB1) was originally described as a nuclear protein that functions as a structural co-factor in transcriptional regulation. However, HMGB1 can also be secreted into the extracellular milieu under appropriate signal stimulation. Extracellular HMGB1 acts as a multifunctional cytokine that contributes to infection, injury, inflammation and immune responses by binding to specific cell-surface receptors. HMGB1 is involved in fibrotic diseases. From a clinical perspective, HMGB1 inhibition may represent a promising therapeutic approach for treating tissue fibrosis. In this study, we demonstrate elevated levels of HMGB1 in the sera in experimental mice or in patients with schistosomiasis. Using immunohistochemistry, we demonstrated that HMGB1 trafficking in the hepatocytes of mice suffering from acute schistosomiasis was inhibited by Glycyrrhizin, a well-known HMGB1 direct inhibitor, as well as by DIC, a novel and potential anti-HMGB1 compound. HMGB1 inhibition led to significant downregulation of IL-6, IL4, IL-5, IL-13, IL-17A, which are involved in the exacerbation of the immune response and liver fibrogenesis. Importantly, infected mice that were treated with DIC or GZR to inhibit HMGB1 pro-inflammatory activity showed a significant increase in survival and a reduction of over 50% in the area of liver fibrosis. Taken together, our findings indicate that HMGB1 is a key mediator of schistosomotic granuloma formation and liver fibrosis and may represent an outstanding target for the treatment of schistosomiasis.